Novel neural network model of power amplifier plus Iq imbalances - Fu, Kai (2014)
Traditionally, the transmitter (TX) IQ imbalances distortion and power amplifier (PA) distortion are separately modeled. In this paper, the behavior of the two distortions are unified, and characterized by a single model. Rectangular structured Focused Time-Delay Neural Network (RSFTDNN) is proposed to uniformly model IQ imbalances and PA distortions. As a result, the physical distortions in the analog circuits are further abstracted. It also saves computation resources in simulation. Unlike the polynomial based model, which suffers from condition number effects and inaccuracy for deeply nonlinear system, the proposed RSFTDNN shows high accuracy. Two cases of real experiments are carried out, where RSFTDNN model shows much better performance than the polynomial based model in the sense of model accuracy.